The emerging role of oral microbiota in oral cancer initiation, progression and stemness - Saikia, Partha Jyoti; Pathak, Lekhika; Mitra, Shirsajit; Das, Bikul (Frontiers in Immunology, 2023)
Oral squamous cell carcinoma (OSCC) is the most prevalent malignancy among the Head and Neck cancer. OSCCs are highly inflammatory, immune-suppressive, and aggressive tumors. Recent sequencing based studies demonstrated the involvement of different oral microbiota in oral cavity diseases leading OSCC carcinogenesis, initiation and progression. Researches showed that oral microbiota can activate different inflammatory pathways and cancer stem cells (CSCs) associated stemness pathways for tumor progression. We speculate that CSCs and their niche cells may interact with the microbiotas to promote tumor progression and stemness. Certain oral microbiotas are reported to be involved in dysbiosis, pre-cancerous lesions, and OSCC development. Identification of these specific microbiota including Human papillomavirus (HPV), Porphyromonas gingivalis (PG), and Fusobacterium nucleatum (FN) provides us with a new opportunity to study the bacteria/stem cell, as well as bacteria/OSCC cells interaction that promote OSCC initiation, progression and stemness. Importantly, these evidences enabled us to develop in-vitro and in-vivo models to study microbiota interaction with stem cell niche defense as well as CSC niche defense. Thus in this review, the role of oral microbiota in OSCC has been explored with a special focus on how oral microbiota induces OSCC initiation and stemness by modulating the oral mucosal stem cell and CSC niche defense.